From print to electronic: the transformation to scientific communication, de Susan Y. Crawford, Julie M. Hurd e Ann C. Weller - Maia, Cristiane (Revista de Biblioteconomia de Brasília, 1998)
CRAWFORD, Susan Y.; HURD, Julie M.; WELLER, Ann C. From print to electronic: the transformation to scientific communication. Medford, NJ : Information Today, 1996. 117 p.